Pengaruh Penambahan Campuran Kapur Tohor dan Kapur Barus (C10H16O) Terhadap Kepadatan Lalat Pada Sampah Organik - Fadya Artha Aristanova; Gunung Setiadi; Isnawati Isnawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: The Effect Of Lime (C10H16O) And Camphor (C10H16O) Against The Density Of Flies On Organic Waste. Fly is a disease-carrying vector so it is important to measure the density for control purposes. One of the controls that is done is on organic waste which is a breading source place of flies. Control is done by affixing the mixture of lime and camphor. This research aimed to determine the effect of mixture of lime and camphor against the density of flies in organic waste that is carried out in the garbage construction site while Southern Loktabat. This type of research is quasi-experimental that experimenting the provision of nine variations of dosage mixture of lime and camphor against the density of flies in organic waste with the organic waste sample was about 0,16m3. This research design used Pretest-posttest design. The analysis using statistical paired sample t-test, Kruskal Wallis test, and Least Significant Differences Test. The measurements showed a decrease in the density of the flies after administration of the lime and camphor mixture. Paired T-test results showed that in each treatment the p-value (2-tailed)